SATUAN POLISI PAMONG PRAJA DAN WILAYATUL HISBAH DALAM PENEGAKAN QANUN DI KABUPATEN ACEH BARAT - Apri Rotin Djusfi; Cut Rina (Jurnal Public Policy, 2017)
The purpose of this research is to know the duties and functions of civil service police unit and wilayatul hisbah in enforcing qanun. Determination of the sample is done by purposive sampling method The research method used qualitative descriptive research. Data collection techniques used three ways: observation, interview, and documentation. The results showed that the tasks of Satuan Pamong Praja Police Unit essentially bind the relationship between members / groups / members of society with the government, basically the three pillars that are related to each other and can not be separated. The three pillars are: First, tranquility is a feeling of the soul of a person (community member) who enjoys his life comfortably free from both physical and spicical disturbances and threats. All activities, creativity, productivity of citizens can be done without fear of fear and worry. Second, peace is an order in a living environment manifested by the existence of human behavior, both personal and as a member of society that adheres to the rules of religious norms, social norms and applicable legislation. Thirdly, the enforcement of regulations (including norms and values) is an important means for the realization of order. Satpol PP and WH Kabupaten Aceh Barat have the task of upholding Qanun and organizing peace and public order and protection of society and enforcement of syariat islam. Keywords: Civil Service Police Unit, the WH, Enforcement Qanun